DEVELOPMENT OF THE PROCEDURE FOR IDENTIFYING ALTERNATIVE SPATIAL PATTERNS BASED ON POLICY SCENARIOS AND SPATIAL CONTIGUITY TO PROMOTE SUSTAINABLE SPATIAL PLANNING AT THE REGENCY/CITY LEVEL (CASE STUDY: BOGOR REGENCY) - Sanni Hafidzah, Dinni
Sustainable spatial planning at the regency/city level is essential for obtaining sustainable development across Indonesia. Nevertheless, due to limitations in implementation mechanisms and methodologies, the concepts of carrying capacity and sustainability have not been thoroughly incorporated into spatial planning in Indonesia, especially at the regency/city levels. The study aims to develop a location-allocation method at the regency/city level to identify alternative land use/land cover locations for spatial planning recommendations. The research method comprises land use/land cover allocation, land suitability assessment by ECOC-SVM, identification of land use/land cover locations based on spatial contiguity, evaluate and develop spatial planning recommendations utilizing a nonweighted overlay relevance matrix. This study provides a procedure for identifying alternative land use/land cover locations based on quantitative carrying capacity indicators for sustainable spatial planning. The results indicate that employing ecological footprint, land suitability, and spatial contiguity can yield optimal alternative land use/land cover locations, reducing land deficits for Dryland Agriculture by 84.08% and completely for other land covers/land uses but still resulting in fragmentation. This study indicates that spatial plan recommendations can be obtained by evaluating the relevance between alternative land use/land cover locations and the spatial plans, utilizing a non-weighted overlay relevance matrix approach. About 27% of Bogor District is advised for zoning alterations, 68% for preserving existing functions, and 5% for modifications based on further observations. The performance of the land suitability model can be enhanced by incorporating physical, disaster-related, or socio-economic parameters. Additionally, land use/land cover has to be assessed through the ecological footprint method which can be represented in spatial planning zones to improve the efficiency of the developing spatial planning recommendations procedure.